1996
DOI: 10.1046/j.1365-2141.1996.d01-1748.x
|View full text |Cite
|
Sign up to set email alerts
|

Exon/intron structure of the human ALL‐1 (MLL) gene involved in translocations to chromosomal region 11q23 and acute leukaemias

Abstract: The acute lymphoblastic leukaemia (ALL)-1 gene on human chromosome 11q23 is the site of many locally clustered chromosomal alterations associated with several types of acute leukaemias, including deletions, partial duplications and translocations. Structurally variant proteins derived from the altered gene presumably cause the malignant transformation of early haemopoietic progenitor cells. According to previously published reports, the gene consisted of at least 21 exons spread over approximately 100 kb. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(92 citation statements)
references
References 20 publications
1
89
1
1
Order By: Relevance
“…The MLL/AF-4 mRNA of patient PCB contained a fusion of MLL exon 11 to AF-4 exon 4 (nomenclature according Nilson et al, 1996Nilson et al, , 1997Marschalek et al, 1997). The AF-4/MLL mRNA of the same patient showed a fusion of AF-4 exon 3 to MLL exon 12.…”
Section: Mapping Of Both Translocation Breakpoints For Three Additionmentioning
confidence: 97%
See 1 more Smart Citation
“…The MLL/AF-4 mRNA of patient PCB contained a fusion of MLL exon 11 to AF-4 exon 4 (nomenclature according Nilson et al, 1996Nilson et al, , 1997Marschalek et al, 1997). The AF-4/MLL mRNA of the same patient showed a fusion of AF-4 exon 3 to MLL exon 12.…”
Section: Mapping Of Both Translocation Breakpoints For Three Additionmentioning
confidence: 97%
“…Breakpoints from patients (circled numbers or letters) were analysed as described in the text and are connected by lines between both breakpoint cluster regions. Numbering of exons of the MLL gene according to Nilson et al (1996) and Marschalek et al (1997); of the AF-4 gene according to Nilson et al (1997) cross-over mechanism could have produced the observed ®nal state. Each of these translocation events was accompanied by deletions, duplications and/or inversions of germline DNA sequences.…”
Section: Characteristic Duplications Deletions and Inversions Are Prmentioning
confidence: 99%
“…There are two numbering systems of exons; the most recent system will be used in this report ( Figure 4). 59 The MLL protein contains a region of three AT-hooks, which have binding capacity to the minor groove of DNA. A domain with binding capacity to hemimethylated DNA is located in the 5Ј portion of the protein encoded by exon 8.…”
Section: Testing and Standardization Proceduresmentioning
confidence: 99%
“…16 Primer sequences are listed in Table 1. Nucleotide and exon numbers are per Chaplin et al 11 for AF10 and Nilson et al 26 for MLL. To confirm the integrity of isolated RNA, a portion of Abl cDNA was amplified using previously described primers.…”
Section: Molecular Analysesmentioning
confidence: 99%